THE CURRENT STATUS OF THE SPECIES HITHERTO ASSIGNED TO HENCKELIA (GESNERIACEAE) - Middleton, D. J.; Weber, A.; Yao, T. L.; Sontag, S.; Möller, M. (Edinburgh Journal of Botany, 2013)
Following recent molecular phylogenetic studies in Old World Gesneriaceae the nomenclatural implications for names in Henckelia are examined. New combinations are made in Codonoboea and Loxocarpus to account for species now excluded from Henckelia. A list is presented in which the current position of all species hitherto assigned to Henckelia is given, including the new combination Henckelia rotundata (Barnett) D.J.Middleton & Mich.Möller. A new combination in Oreocharis is made.